Memorias del tránsito - Griselda Späth (Les Cahiers ALHIM)
Different occupations mean for those who develop them, to change the place of residence. In Argentina, this applies to police, banking, professionals of different areas, footballers, railway workers, diplomats, ranger, prosecutors, etc. More or less regularly, within or outside the country, to maintain employment or promotion; these persons move with their families, for a time period, forming what Silvia Korenblum (2003) defines as "families in transit". The aim of this work, and the doctoral thesis in which it is developed, is to analyze the way in which families in transit children, build their identity.  From a biographic approach, depth interviews were conducted to construct life stories. Trough out the analysis of the interviews, the building blocks of memory (Pollak: 1992); were tracked, distinguishing events, people and significant sites for each individual in his migratory trajectory.